Nutrient thresholds to protect water quality and coral reefs. (October 2020) - Houk, Peter; Comeros-Raynal, Mia; Lawrence, Alice; Sudek, Mareike; Vaeoso, Motusaga; McGuire, Kim; Regis, Josephine
Abstract: Establishing nutrient thresholds to protect coral reefs is difficult because water quality is dynamic and shifts with many environmental factors. We examined the contribution of natural and human factors in predicting water quality at the base of 34 streams on a high tropical Pacific island. Mixed regression models revealed that rainfall, sea-surface temperature, and windspeed were fixed factors predicting dissolved inorganic nitrogen (DIN) concentrations at the base of all watersheds. In contrast, human influences were captured as random components of variation associated with site-based differences. The novel modeling approach using temporal and spatial data provided daily-loading simulations that were used to evaluate exceedance criteria, defined as the percent of time each watershed exceeded a suite of DIN thresholds. Exceedance criteria were considered alongside biological data to recommend a 0.1 to 0.15 mg l −1 benchmark to protect coastal water quality and coral reefs surrounding Tutuila, American Samoa. Highlights: Factors driving nutrient delivery from watersheds to coral reefs were identified. Mixed-regression models partitioned human versus natural factors. Nutrient load simulations were used to identify potential legislative thresholds. Biological data were incorporate to calibrate thresholds. The transparent process is flexible to differing assumptions and locations.